Molecular characterization of a collection of the tropical multipurpose shrub legume Flemingia macrophylla - Andersson, Meike S.; Peters, Michael; Schultze-Kraft, Rainer; Gallego Sánchez, Gerardo J.; Duque E., Myriam Cristina (Springer, 2006)
Random amplified polymorphic DNA (RAPD) markers were used for assessing genetic diversity and its structure in a collection of the drought-tolerant, tropical multipurpose shrub legume Flemingia macrophylla (Willd.) Merrill. The species is especially suited to low-input smallholder production systems and is used as dry season forage supplement, live soil cover, mulch and living barrier, among others. Genetic groups identified by RAPD analysis related closely to four morphotypes revealed by multivariate analysis of morphological, agronomic and forage quality characteristics. Overall genetic diversity in the collection was moderate (H T = 0.241), with 79% differentiation among and high genetic similarity (GS) within groups (0.672 0.965). Results indicate a closer relationship of the semi-erect morphotypes M3 and M4 with F. stricta rather than with the erect morphotype M1. The latter was genetically the most depauperate, followed by morphotypes M2 and M4. New evidence is provided that non-Asian accessions collected in Africa and South America are derived from introduced Southeast Asian material. Furthermore, RAPD data suggest the presence of duplicates in the collection, especially in the overrepresented erect morphotype M1.